Tillage and evaporativity effects on the drying characteristics of a silty loam: Evaporation prediction models - Mwendera, E.J.; Feyen, J. (Elsevier, 1997)
Evaporation of water from 'micro-lysimeters' collected from four types of field tillage treatments, namely, ploughed to a depth of 30cm (P), ploughed and then harrowed (P + H), ploughed, harrowed and rolled (P + H + R) and untilled (UNT) plots, was studied in a controlled laboratory environment at five rates of atmospheric evaporativity close to those found under field conditions. Evaporative demand (E(o)) in the field was determined by measuring evaporation from open water with a recording evaporation balance. Actual evaporation from the field soil was determined by daily measurement of water content in the top 10 and 20cm layers. Drying was best described by a modified version of the square root of time behaviour model of T.A. Black, W.R. Gardener and G.W. Thurtell (The prediction of evaporation drainage and soil water storage for a bare soil. Soil Sci. Am. Proc., 33: 655-660, 1969) and a simple parametric model similar to that proposed by J.J.T.I. Boesten and L. Stroosnijder (Simple model for daily evaporation from fallow tilled soil under spring conditions in a temperate climate. Neth. J. Agric. Sci., 34: 75-80, 1986). The parametric model was incorporated in a model describing water dynamics in a silt loam soil (Typic Hapludalf) on field plots located near Ter Munck, 5 km southwest of Leuven, Belgium. The results show that drying characteristics of tilled soils are influenced by factors such as tillage depth, surface micro-relief, soil type, and the nature of the evaporative demand, and that it is possible to incorporate such effects in evaporation models. However, more research is needed to study the combined effects of tillage type and depth and atmospheric evaporativity on the drying characteristics of different soils, and to compare the relative effect of radiation-dominated evaporativity on the evaporation parameters with that of wind-dominated evaporativity.